Examining The Role of Strategy in Corporate Turnarounds from A Resource Base View: A Historical Analysis - Bhatia, Manpreet Singh (2010)
Prior research on turnarounds has given considerable importance to measures like retrenchment, cost control and other operative measures, but the role of strategic change has been undermined so far. This work is centred at analysing the role of strategy in turnarounds. For the purpose of study an already identified turnaround company is chosen from Wild (2010) paper, to have no doubts regarding its qualification to the criteria. A case study approach prevalent to Business History Literature is adopted to analyse the role of strategic factors initiating turnarounds, in the light of resource base view theory. Special attention has been given to the criteria of defining company’s expansion in terms of organic & acquisitive growth, and how they have an impact in turnaround. The study finds that strategic factors like: Strategic Acquisitions, Diversification/ Refocusing and Changes in Management can play a major role in reviving company’s performance. It reveals that selection of an appropriate case following a contextual method of analysis in the light of resource base view theory can have an impact on the research findings. Results of this research unveils that strategy has consequences on company’s performance and play an important role in a successful turnaround.